Wear behaviour of polyethylene glenoid inserts against PyroCarbon humeral heads in shoulder arthroplasties. (March 2020) - Ramírez-Martínez, Israel; Smith, Simon L.; Trail, Ian A.; Joyce, Thomas J.
Abstract: The generation of polyethylene wear debris, and the subsequent tissue reaction to such debris is considered to be a limitation in the long-term survival of shoulder arthroplasties. The purpose of this study was to investigate, for the first time, the wear of a novel PyroCarbon-on-Polyethylene (PyCoP) shoulder arthroplasty system. A 5 million cycle wear test was performed on PyroCarbon humeral heads, which were articulated against commercially available polyethylene glenoid insert components to form an anatomic total shoulder arthroplasty (aTSA). A "Repeat-motion-load" physiological combined cycle was applied using the unique Newcastle Shoulder Wear Simulator. Wear was assessed gravimetrically, and the change of the surface roughness was measured with a non-contacting profilometer. The mean wear rate of the ultra-high molecular weight polyethylene (UHMWPE) components was 19.3 ± 9.5 mm 3 /million cycles after 5 million cycles of testing. The roughness value, Sa, of the UHMWPE glenoid inserts, reduced, changing from 296 ± 28 nm Sa to 32 ± 8 nm Sa . In contrast, the mean roughness of the PyroCarbon humeral heads remained in the same range (21 ± 2 nm Sa to 20 ± 10 nm Sa ). There was no reduction in weight (no measurable wear) of the PyroCarbon humeral heads over the duration of testing. This study is the first to describe the wear performance of UHMWPE glenoid inserts against PyroCarbon humeral heads. No significant difference in the wear of UHMWPE was found in comparison with published studies. Highlights: This study investigated for the first time the wear performance of UHMWPE glenoid inserts against PyroCarbon humeral heads. Polyethylene wear rate against PyroCarbon counterparts was similar to previous in vitro studies on metal-on-polyethylene. PyroCarbon components did not exhibit a loss in weight or an appreciable change in surface roughness over the test duration.